Construction of the ABCE-ring structure of talatisamine via decarboxylative radical cyclization. Issue 35 (28th August 2020) - Minagawa, Kosuke; Kamakura, Daiki; Hagiwara, Koichi; Inoue, Masayuki
Abstract: Talatisamine (1 ) is a C19 -diterpenoid alkaloid with a synthetically challenging hexacyclic ABCDEF-ring structure. Herein we report a radical-based strategy for constructing the 6/7/5/6-membered ABCE-ring 8a . After assembling the 3 known fragments, an AE-ring, an allylstannane, and a C-ring, irradiation of the ACE-ring with Hg lamp in the presence of phenanthrene and 1, 4-dicyanobenzene promoted decarboxylative formation of the C11-bridgehead radical, which cyclized into the 7-membered B-ring with stereoselective installation of the C9, 10-tertiary carbons of 8a . Graphical abstract: Image 1 Highlights: Talatisamine, a C19-diterpenoid alkaloid, has a complex 6/7/5/6/6/5-membered hexacyclic ABCDEF-ring skeleton. We report the synthesis of 6/7/5/6-membered ABCE-ring framework from 3 simple components. The 7-membered B-ring was constructed by utilizing a photoinduced decarboxylative radical reaction. Phenanthrene and 1, 4-dicyanobenzene enabled the formation of the hindered radical by single-electron oxidation.